RELASI BENTUK, FUNGSI, DAN MAKNA JEMBATAN PENYEBERANGAN ORANG (JPO) KAWASAN JALAN JENDERAL SUDIRMAN, JAKARTA BAGI MASYARAKAT URBAN: The Relation of Form, Function, and Purpose of Crossing Bridge on Jendral Sudirman District in Urban Society - Awang Eka Novia Rizali; Elda Franzia Jasjfi; Erick Teguh Leksono; Charles S. Marpaung; Joseph Setiawan Cahyadi (Jurnal Dimensi Seni Rupa dan Desain, 2023)
The Jalan Jenderal Sudirman area, Jakarta, is a rapidly developing urban center area. The People's Crossing Bridge (JPO) in the Jalan Jenderal Sudirman area, Jakarta has undergone revitalization. The six research objects, namely JPO Ratu Plaza – Senayan, JPO Gelora Bung Karno (GBK), JPO Polda Metro Jaya, JPO without roof in front of Indofood Tower, JPO Pinisi, and JPO Dukuh Atas, have various forms as a result of the DKI Jakarta Regional Government revitalization, but the relationship with function and meaning. Therefore this study aims to understand the relationship between the form, function, and meaning of JPO products in the Jalan Sudirman area, Jakarta, which represents the behavior and activities of urban communities as users. The research method used is descriptive qualitative, to elaborate and describe descriptively the relation of form, function, and meaning of JPO to users, especially urban communities. The results of this study reveal that the six JPOs in the Jalan Jenderal Sudirman area, Jakarta, have become a representation of the behavior and activities of the Jakarta urban community as users. The city of Jakarta as a dynamic metropolis is reflected in the forms of the JPO and the behavior of its users. Keyword: design, pedestrian bridge, Jakarta, urban society